Green fabrication of composite cathode with attractive performance for solid oxide fuel cells through facile inkjet printing - Li, Chao; Chen, Huili; Shi, H.; Tade, Moses; Shao, Zongping (Elsevier SA, 2015)
The inkjet printing technique has numerous advantages and is attractive in solid oxide fuel cell (SOFC) fabrication, especially for the dense thin electrolyte layer because of its ultrafine powder size. In this study, we exploited the technique for the fabrication of a porous SDC/SSC composite cathode layer using environmentally friendly water-based ink. An optimized powder synthesis method was applied to the preparation of the well-dispersed suspension. In view of the easy sintering of the thin film layer prepared by inkjet printing, 10 wt.% pore former was introduced to the ink. The results indicate that the cell with the inkjet printing cathode layer exhibits a fantastic electrochemical performance, with a PPD as high as 940 mW cm−2 at 750 °C, which is comparable to that of a cell prepared using the conventional wet powder spraying method, suggesting a promising application of inkjet printing on electrode layer fabrication.